2019
DOI: 10.1017/s0950268819000840
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Bordetella pertussis toxin antibodies in children and adolescents in Tunis, Tunisia

Abstract: Pertussis remains a public health concern in most countries. This cross-sectional study aims to investigate the distribution of pertussis toxin antibodies (anti-PT IgG) in Tunisian children and adolescents aged 3–18 years, to define optimal age for booster vaccination. Anti-PT IgG concentrations of enrolled participants were measured using commercial enzyme-linked immunosorbent assay. Concentrations were classified as: indicative of current/recent infection if ⩾100 IU/ml, indicative of recent exposure to Borde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In Tunisia, 12.3% of adolescents (13-18 years) were seropositive with anti-PT IgG antibodies indicative of recent infection/exposure to BP. 12 In a Hungarian study, 14.8% of the adults population screened were seropositive. 13 The majority of the population investigated (85.2%) were considered at increased risk of BP infection due to waning immunity.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In Tunisia, 12.3% of adolescents (13-18 years) were seropositive with anti-PT IgG antibodies indicative of recent infection/exposure to BP. 12 In a Hungarian study, 14.8% of the adults population screened were seropositive. 13 The majority of the population investigated (85.2%) were considered at increased risk of BP infection due to waning immunity.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Bordetella pertussis (BP) has continued to spread even though infants and children have a high vaccine coverage. 12 Adolescents and adults are identified as the primary source of infection for newborns and young infants. 13 It is, therefore, of great importance to prevent and early detect pertussis among those populations.…”
Section: Introductionmentioning
confidence: 99%
“…There were five studies which reported epidemiology data for pertussis in Africa, namely Senegal [ 27 ], Tunisia [ 28 ], Algeria [ 29 ], Nigeria [ 30 ], and Uganda [ 31 ], and seven studies which reported sero-epidemiology in Senegal [ 32 ], Cameroon [ 33 ], South Africa [ 34 ], Tunisia [ 35 , 36 ], Morocco [ 37 , 38 ], and Gambia [ 39 ]. There were seven studies with mortality data including Nigeria [ 30 , 40 ], Ethiopia [ 41 ], Morocco [ 42 ], South Africa [ 43 , 44 ], and Senegal [ 27 ].…”
Section: Search Resultsmentioning
confidence: 99%
“…A seroprevalence study among healthcare workers (HCWs) at the same children's hospital during the same surveillance period confirmed that pertussis was circulating in hospital settings and affecting HCWs in close contact with infants [35]. [36].…”
Section: Tunisiamentioning
confidence: 90%
“…The EUROIMMUN kit has a high specificity and sensitivity compared to the other commercialised kits summarised in the Annex Table. Although this kit is commonly used for diagnosis, it has previously been used to estimate seroprevalence [23]. All experiments were conducted at the laboratories of Experimental Bacteriology of the Institut Pasteur de Madagascar (IPM) according to the manufacturer's manual.…”
Section: Methodsmentioning
confidence: 99%